COFFEE CULTURE IN INDONESIA: EMBRACING LOCALITY THROUGH COFFEE CENTER - Joanne, Gracelynn
Indonesia ranks as the world’s fourth-largest coffee bean producer. Indonesia has a wide range of coffee beans that translates into a remarkable production number of 794.8 thousand tons in 2022. Beyond the production figures, Indonesia also has a lot of cultural expressions towards coffee such as the world-renowned Kopi Luwak, Kopi Tubruk, to Kopi Tarik. These diversity showcase the nation’s favor over coffee, placing Indonesia as the second-highest coffee consumer in Asia and the Pacific. Data also shows that Indonesia’s coffee consumption is expected to reach 4.8 million bags in the 2022/23 consumption year. The growth alighs with the significant growth of coffee shops in Idnoensia, with the number of establishments witnesing a 170% surge between 2016 and 2019. Despite the impressive amount of production and consumption, a gap in coffee knowledge in Indonesia does exist. To adress this, the establishment of coffee center emerges as a potential solution. The coffee center offers non-formal education, tourism, and consumption platform, also to increase the economy value of Indonesian coffee. This coffee center aims to not just provide visitors with Indonesia’s rich coffee heritage insights but also offer the coffee consumption.